Pengaruh Enviromental, Social dan Governance Disclosure terhadap Profitabilitas Perusahaan Sektor Makanan dan Minuman di Indonesia - Yesha Dewanti Sijabat; Rizma Amalia; Stefanny Margaretha Simalango; Ade Yuniati; Golda Belladonna Umbing (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In the modern era, companies are assessed not only based on financial performance but also on how they manage environmental, social, and governance (ESG) impacts. ESG disclosure has become a key consideration for investors in evaluating corporate sustainability, particularly in the food and beverage sector in Indonesia. This study aims to analyze the effect of ESG disclosure on the profitability of food and beverage companies listed on the Indonesia Stock Exchange (IDX). The research employs a quantitative method with a multiple linear regression approach to analyze panel data. Data were obtained from annual reports and sustainability reports of companies for the 2021-2023 period. The research sample was selected using a purposive sampling method based on ESG disclosure criteria and the availability of profitability data. The analysis includes descriptive statistics, classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation), as well as hypothesis testing using t-tests and F-tests. The findings reveal that, partially, the environmental, social, and governance disclosure variables do not have a significant effect on profitability (measured by Return on Assets/ROA). Simultaneously, these three variables also show no significant relationship with company profitability. The low coefficient of determination (R² = 0.018) indicates that profitability variance is predominantly influenced by factors outside of ESG disclosure.